Youth awareness towards energy saving - Salleh N.S.M. (American Scientific Publishers, 2023)
Energy is central to human existence. The side effect of highly demand energy can be seen from the climate change and other environmental effects. In predicting the nation future towards energy saving (ES), energy usage driven by youth attitude can be one of the factors. This paper focuses on a preliminary study in exploring youth awareness of ES. We have carried out one of data gathering technique, survey to find the level of awareness among youth in higher-level institution. The results show that almost 76% of the respondents are moderately aware of the ES. 2016 American Scientific Publishers. All rights reserved.